Chinese Herbal Medicine Usage Reduces Overall Mortality in HIV-Infected Patients With Osteoporosis or Fractures - Ho, Mao-Wang; Li, Te-Mao; Li, Ju-Pi; Chiou, Jian-Shiun; Chiu, Mu-Lin; Chen, Chao-Jung; Cheng, Chi-Fung; Tsai, Fuu-Jen; Wu, Yang-Chang; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; et al. (Frontiers in Pharmacology, 2021)
The survival of patients with HIV has greatly improved, due to Anti-Retroviral Therapy (ART). However, long-term HIV survivors often develop serious bone abnormalities, possibly due to the interplay of osteoblasts, osteoclasts, HIV ad ART. We evaluated in a nation-wide study in Taiwan the effect of Chinese herbal medicine (CHM) on overall mortality in HIV patients with osteoporosis or fractures. Enrollment period was between 1998 and 2011. Patients with osteoporosis or fractures before the HIV infection, and those with less than 14 days CHM use, were excluded. This left 498 patients, 160 CHM users, 338 without CHM. Univariate Kaplan-Meier and multivariate Cox regression analysis were used to compare the overall mortality in these 2 groups. Due to the nature of Chinese medicine, CHMs inevitably varied. We therefore also used rule mining and network analysis to determine which major CHM clusters were prescribed to the patients. CHM users had a much Lower mortality (hazard ratio (HR) = 0.43, 95% confidence interval (CI): 0.24-0.77, p < 0.005) and higher survival (p = 0.004, log-rank test). Although the CHMs greatly varied, network analysis identified one main cluster of strongly related CHM combinations (Chuan-Xiong-Cha-Tiao-San (CXCTS), Gan-Cao (GC; Glycyrrhiza uralensis Fisch.), Liu-He-Tang (LHT), Huang-Qin-Tang (HQT), Jia-Wei-Ping-Wei-San (JWPWS), and Dang-Gui-Long-Hui-Wan (DGLHuiW)). CHM as an additional treatment strongly improves overall survival in HIV-infected patients with osteoporosis and fractures.